2022
DOI: 10.2147/dddt.s381611
|View full text |Cite
|
Sign up to set email alerts
|

Remimazolam for the Prevention of Emergence Delirium in Children Following Tonsillectomy and Adenoidectomy Under Sevoflurane Anesthesia: A Randomized Controlled Study

Abstract: Purpose To identify the effectiveness of remimazolam at the end of tonsillectomy and adenoidectomy for preventing emergence delirium in children under sevoflurane anesthesia. Patients and Methods One hundred and four patients aged 3–7 years scheduled for tonsillectomy and adenoidectomy under sevoflurane anesthesia were recruited. Patients were randomly assigned to receive either remimazolam 0.2 mg kg –1 (intervention, n=52) or 0.9% normal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…We considered that the incidence of delirium was slightly higher because RMMZ is a benzodiazepine; however, in previous studies, the correlation between RMMZ and delirium remained controversial [ 29 , 30 ]. Previous studies have demonstrated that RMMZ prevents emergent delirium in children [ 31 ]. Additional large-scale studies are required to evaluate these differences.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that the incidence of delirium was slightly higher because RMMZ is a benzodiazepine; however, in previous studies, the correlation between RMMZ and delirium remained controversial [ 29 , 30 ]. Previous studies have demonstrated that RMMZ prevents emergent delirium in children [ 31 ]. Additional large-scale studies are required to evaluate these differences.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Remimazolam can not only effectively relieve preoperative anxiety but also reduce the risk of postoperative delirium and mania in children after sevoflurane anesthesia, which contributes to shortening hospitalization, reducing the medical burden, and improving parent satisfaction. 6 , 22 Remimazolam has not been approved by the FDA for use in pediatric patients and was first approved in 2020 for general anesthesia in adults ( Figure 4 ). At present, remimazolam is only used in a few licenced health care facilities.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
“…A prospective, double-blind, randomized, placebo-controlled study showed that the risk of delirium after anesthesia with sevoflurane was reduced by the intraoperative administration of remimazolam (0.2 mg/kg) before the end of surgery in children aged 3 to 7 years undergoing adenotonsillectomy, without prolonging recovery time in the postanesthesia care unit (PACU). 22 Mo et al 6 found that a low of remimazolam (0.1 mg/kg) significantly reduces the incidence of emergence agitation without affecting recovery and improves the safety of preschoolers undergoing day surgery after discharge. The dose‒response relationship and long-term effects of remimazolam on reducing the incidence of postoperative delirium and emergence agitation after anesthesia with sevoflurane need further assessment in the future.…”
Section: Current Status Of Applications Of Remimazolammentioning
confidence: 99%
“…To determine whether remimazolam decreases the risk of emergence excitation in children, Yang et al 44 randomized 104 children aged 3 to 7 years having tonsillectomy to receive either 0.2 mg/kg remimazolam or saline placebo before emergence from general anesthesia; patients were assessed for emergence excitation for up to 30 minutes after anesthesia using structured scoring. Rates of emergence excitation were significantly lower in the remimazolam group compared with the placebo group (12% vs. 44%, respectively; P <0.05).…”
Section: Effect Of Remimazolam On Cognitive Changes Associated With A...mentioning
confidence: 99%